Influence of oral function on the occurrence of crowding in Japanese children: an epidemiological study using longitudinal data from the general population - Yui Fujiwara; Kaori Ishii; Toshio Wani; Sho Kuroe; Yusuke Suzuki; Shinichi Negishi (Clinical and Investigative Orthodontics)
Purpose To observe the morphological and functional changes associated with crowding by longitudinally following the same individuals during their mixed dentition period.Methods Subjects were 66 individuals with longitudinal data of mixed dentition, obtained every other year from 2012 to 2019. At T1 (when incisors and first molars had erupted and deciduous canines remained) and T2 (when permanent canines had fully erupted), Measurements were taken to observe and analyse trends in morphological and functional changes over time, without interventions. Morphometric measurements included three-dimensional evaluation of palatal, dentition and first molar tooth movement, and oral function measurements included width of the masticatory path, occlusal force and lip closure force.Results From T1 to T2, the palatal width diameter (PW), palatal depth (PD), dental arch width diameter (3AW, 6AW), and maxillary first molar buccolingual inclination (BLI) increased significantly, whereas the dental arch length diameter (AL’, AL) and the rotation angle of the maxillary first molars (RA) decreased significantly. Spearman’s rank correlation coefficients showed that 3AW and RA were significantly associated with the masticatory path width and occlusal force.Conclusions This study suggests that oral function during growth may be associated with changes in morphological characteristics that influence crowding.